As jogadas de Sólon e a esperteza dos Atenienses: Plutarco e o uso irónico da teatralidade e das metáforas na Vita Solonis - Leão, Delfim (2013)
Throughout his life, Solon intervened at different times in the Athenian political scene, usually against a backdrop of great instability. Such was the case when he found a way to skirt legal impediments and to exhort his fellow citizens to recapture their own self-esteem, by exhibiting a fainted mania while performing the elegy for Salamis. The playful character of Solon can also be detected in the way he decided to label his first emblematic reform – the seisachtheia, the revolutionary cancelling of debts, which he literally named as ‘shaking off of burdens’. This paper intends to discuss the way Plutarch displays some of his discrete irony even when depicting a statesman as serious and paradigmatic as Solon.